Saline tolerant of marine endophytic fungi from Teluk Kemang Malaysia – a rich source of bioactive material - Putri Syazwina Megat Abdul Latif; Norfarhan Mimi Mohd Noor; Shazahuda Mazlan; Norasyikin Razali; Kalavathy Ramasamy; Siti Alwani Ariffin (Penerbit Universiti Kebangsaan Malaysia, 2022)
Endophytic fungi have been reported to have the potential as an alternative source for active metabolites in drug discovery. In a recent study, bioactive compounds were isolated from marine endophytic fungi in Malaysia. However, marine endophytic fungi were not identified. In this study, therefore the 18 endophytic fungi that were isolated from eight marine seaweeds collected from Teluk Kemang Negeri Sembilan, Malaysia were identified and evaluated for their antimicrobial activity. Out of 18 marine endophytic fungi, 11 of them were successfully identified based on internal transcribed spacer (ITS) sequencing. Of the 11, six marine endophytic fungi (MV, CN, CS1, CS2, ED1, PA1) identified were Aspergillus sp, whereas the other marine endophytic fungi isolates (UF, ED2, PA2) had sequences that were similar to Exophiala dermatitidis, Diaporthe pseudomangiferae, Arthrinium xenocordella, Phanerochaete carnosa, and Psathyrella purpureobadia respectively. A significant antifungal activity against three pathogenic fungi was exhibited by using the disc diffusion method. Eight extracts (CN, CN1, MV, MV1, ED1, ED11, ED2, ED21, PA7, PA71) exhibited antifungal activity ranging from 6.5 mm ± 0.71 mm to 12mm±1.41 (p<0.05) against Candida albicans and Trichophyton rubrum. The fungicidal effect of CN1 and ED11 extracts was detected at a lower concentration tested (0.625mg/mL) and the diameter of zone inhibitions for these two extracts (CN:9.0 mm ± 0.00 and ED11: 10.5 mm ± 0.71) were even bigger when compared to Amphotericin B (7.5mm ± 0.71). This study also showed that the salinity (additional 3% sea salt) influenced the growth, spore production, and antifungal properties of the marine endophytic fungi. Marine endophytic fungi isolated from the selected seaweeds in the present study, therefore represent a promising source of antifungal and warrant further detailed investigation.